2017
DOI: 10.23736/s0375-9393.17.11681-0
|View full text |Cite
|
Sign up to set email alerts
|

Early versus late tracheostomy in pediatric intensive care unit: does it matter? A 6-year experience

Abstract: BacKgroUnD: the aim of this study is to examine the clinical data of children who underwent tracheostomy during their stay in Pediatric intensive care Unit (PicU), in order to describe the relationship between the timing of tracheostomy, the length of PicU stay and the occurrence of ventilator-associated pneumonia (vaP). MetHoDs: this is a retrospective cohort study that collects all patients undergoing tracheostomy during their PicU stay over a six-year period. Data collection included PicU length of stay, da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
(14 reference statements)
1
12
0
Order By: Relevance
“…For long-term ventilation after tracheostomy, the meta-analysis of Pizza, McLaughlin, and Lee showed a non-significant risk ratio ( p = 0.32) for late and early tracheostomy. 65 , 66 , 67 For successful decannulation, the meta-analysis of Lee and Pizza also showed no difference ( p = 0.98). 66 , 67 Early tracheostomy was associated with higher probabilities of discharge to home in McLaughlin (29.8% versus 14.9%), and Sheehan (50% versus 9.2%, p < 0.001).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…For long-term ventilation after tracheostomy, the meta-analysis of Pizza, McLaughlin, and Lee showed a non-significant risk ratio ( p = 0.32) for late and early tracheostomy. 65 , 66 , 67 For successful decannulation, the meta-analysis of Lee and Pizza also showed no difference ( p = 0.98). 66 , 67 Early tracheostomy was associated with higher probabilities of discharge to home in McLaughlin (29.8% versus 14.9%), and Sheehan (50% versus 9.2%, p < 0.001).…”
Section: Resultsmentioning
confidence: 93%
“…The search did not return any randomized trials. The authors found eight studies 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 that compared the prognoses of patients undergoing “early” or “late” tracheostomy: in five, “early tracheostomy” was defined as being performed before 14 days of mechanical ventilation, and “late,” after this period. In two studies, “early” was defined as before seven days post-trauma injury, and, in one, as before ten days of ventilation ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Motor vehicle collision was the most common mechanism of injury (54.1%), and 47.0% had a severe thoracic injury and 19.3% had a severe abdominal injury. Median ISS was 22 (IQR, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In the TBI group, median GCS was 7 (IQR, 3-12, includes only n = 3,270 with valid arrival GCS), and 18.6% underwent craniotomy.…”
Section: Patient Demographicsmentioning
confidence: 99%
“…Some studies have shown fewer ventilator days, shorter ICU and hospital length of stay, and/or lower risk of pneumonia in patients with early tracheostomy compared with those with later tracheostomy; however, other studies have shown no difference (20)(21)(22)(23)(24)(25)(26). These studies are limited by not accounting for differences in tracheostomy indication (e.g., traumatic brain injury [TBI], prolonged respiratory failure, spinal cord injury, or craniofacial injury) (14,22,23,26). An additional limitation of prior studies is the heterogeneity in the definition of "early" versus "late" tracheostomy.…”
mentioning
confidence: 99%